2006
DOI: 10.1097/01.ajp.0000210914.72794.bc
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related Catastrophizing in Healthy Women Is Associated With Greater Temporal Summation of and Reduced Habituation to Thermal Pain

Abstract: These preliminary findings highlight the importance of coping in shaping individuals' responses to noxious stimuli, and suggest that interventions that decrease pain catastrophizing may reduce the burden of acute and chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
5
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 201 publications
(188 citation statements)
references
References 72 publications
12
170
5
1
Order By: Relevance
“…Catastrophizing has also been associated with indices of central sensitization, and dysfunction of descending noxious inhibitory control, both of which have also been discussed as processes underlying the pathogenesis of multisite pain 19,29,37 .…”
Section: Psychology Of Multisite Pain 16mentioning
confidence: 99%
“…Catastrophizing has also been associated with indices of central sensitization, and dysfunction of descending noxious inhibitory control, both of which have also been discussed as processes underlying the pathogenesis of multisite pain 19,29,37 .…”
Section: Psychology Of Multisite Pain 16mentioning
confidence: 99%
“…This was done because laboratory-based studies have highlighted the importance of specifying the context in which catastrophizing is assessed. [15][16][17] Results in our sample showed that the internal consistency was high for the in vivo PCS total score (a = 0.90).…”
Section: Methodsmentioning
confidence: 71%
“…11,100,101,118 Follow-up studies have also shown that the initial catastrophization ideas are related to the level of pain that a patient will point out after a surgical procedure 41,88 or after other painful conditions. 23,24,111,126 Although the exact mechanisms by which catastrophization affects the experience of pain and disability are not well known, it has been suggested that it influences the focusing of one's attention to the painful or potentially painful process. People, who catastrophize, have difficulties in not focusing on the painful or threatening stimulus.…”
Section: Catastrophizationmentioning
confidence: 99%
“…This suggests that catastrophization plays a facilitator role in the pain perception process. 23 Catastrophization can be clinically measured by the catastrophization subscale of the Coping Strategies Questionnaire (CSQ). 99 There is another specific tool to measure it as well, the Pain Catastrophizing Scale (PCS).…”
Section: Catastrophizationmentioning
confidence: 99%